Geoscience Department of Universiti Teknologi PETRONAS / Fatin Nurhana Jumisdar - Jumisdar, Fatin Nurhana (Universiti Teknologi MARA, Perlis, 2023)
This internship report pertains to a highly commendable six-month industrial training experience at the Geoscience Department of Universiti Teknologi PETRONAS in Seri Iskandar, Perak. I have been designated for employment in the Geoscience Department under the supervision of Dr. Khairul Arifin B. Mohd Noh, the Chair of the Department. The duration of the industrial training that I completed at the "Geoscience Department, Universiti Teknologi PETRONAS" spanned a period of 24 weeks, commencing on March 1, 2023, and concluding on August 15, 2023. The duration of 24 weeks provided a highly enriching and positive experience due to its various benefits. I was granted the opportunity to engage in geoscience and educational experience, primarily focused on administrative affairs and the geoscience work environment. This encompassed a range of activities, including data management and interaction with students and personnel. The experiences were distinct and indelible. By conducting a thorough examination of the department's present condition, the objective is to provide insight into the diverse elements that contribute to its achievements and identify potential avenues for enhancement. The subsequent sections provide a comprehensive analysis of the strengths, weaknesses, opportunities, and threats pertaining to the Geoscience department. Based on a comprehensive analysis of relevant research and empirical evidence, this report aims to present a set of pragmatic suggestions that can assist the department in attaining its overarching objectives while effectively addressing the forthcoming obstacles. By capitalizing on its inherent advantages, seizing potential prospects, and effectively tackling areas of improvement and challenges, the Geoscience Department can establish itself as a leader in scientific exploration and significantly contribute to the betterment of our planet. Additionally, this approach will foster a conducive work environment that attracts and retains high-performing individuals within the department.